Capital Appropriations and the Investment Decision - Campagna, Anthony S. (The Review of Economics and Statistics, 1968)
EMPIRICAL studies of the investment decision have been restrained by the lack of data to the examination of investment expenditures anticipated or realized. A consequence of this empirical bias may be the diversion of attention away from the complete decision-making process and to the misleading impression that the investment decision is primarily and essentially one of timing and financing investment outlays. (See, however [2, 5, 6, 12-14].) The underlying hypothesis of this paper is that there are two investment decisions: The first, reflecting long-run plans and expectations, is whether or not to invest at all; the second, chronologically, is when to make and how to finance the actual expenditures. The latter is likely to be a function of the actual market conditions faced or the short-term expectations of those market conditions. While the need to include plans and expectations into the analysis may be fairly obvious, the necessary algebra remains elusive. However, objective data can capture most of what we need to know about expectations, leaving the algebra to be uncovered by empirical research. All that is needed are data that can be deemed to embody expectations without necessarily specifying their origin. Accordingly, a rather general model will be developed using capital appropriations data and initial conditions, which will illustrate the method proposed. In this paper, only the first decision, the formal commitment to invest, will be examined further. Given the capital appropriation, the question is what constitutes the set of relevant initial conditions and how much of the capital appropriations can be accounted for by reference to it. If the hypothesis of two investment decisions is correct, then there is a subset of initial conditions influencing this first investment decision and another subset which does not. This is essentially an empirical question. To examine the relationship between capital appropriations and initial conditions, cross-section data are used. They are generally regarded as reflecting long-run tendencies, and since the first decision is more or less a stock one, variables which vary over time and thus more appropriate for the flow decision prices, interest rates are eliminated. Two years have been selected for study 1956 and 1961-which are the best years available in the basic data. These years exhibit roughly the same movements in the business cycle and are far enough apart so that structural changes are permitted. The initial approach to the data and the immediate task for the present is to determine: (a) What the relationship is between capital appropriations and various selected variables for selected industries in each of the two years; (b) Whether the structure of expectations the same variables dominating was the same for each industry in 1956 as in 1961; (c) Whether there are significant differences among industries in the variables which are important. The data used were supplied by the National Industrial Conference Board (NICB) which since 1953 has conducted a quarterly survey of capital appropriations for the top corporations in the United States. These are large corporations and account for a sizeable proportion of investment expenditures. For a more detailed description of the data see Cohen [13]. Out of seventeen industrial groups of NICB, seven were selected for study: Primary Iron and Steel, Primary Nonferrous Metals, Machinery (except electrical), Fabricated Metals, Food and Beverages, Textiles Mill Products, and Paper and Allied Products. These industries were selected for their possible differing structure of expectations and because they rep* The author is an Assistant Professor of Economics at the University of Vermont. Parts of this paper are based on his Ph.D. dissertation, Expectations and The Investment Function (Rutgers The State University, Jan. 1966). He is indebted to Rutgers The State University for grants received, and to The Bureau of Economic Research at Rutgers University for additional financial support. The author is also indebted to K. K. Kurihara and M. Dutta for many helpful suggestions.